Automated driving: Safety blind spots. (February 2018) - Noy, Ian Y.; Shinar, David; Horrey, William J.
Highlights: Automated driving has the potential to improve traffic safety in the long term. For the foreseeable future, partially AD present unwitting consequences. Drivers' role will change and lead to potential confusion or traffic conflicts. Human factors research is needed address new questions of partial automation. Integration within the broader cyber-physical world is an emerging challenge. This paper identifies areas that require explicit and urgent scientific exploration. Abstract: Driver assist technologies have reached the tipping point and are poised to take control of most, if not all, aspects of the driving task. Proponents of automated driving (AD) are enthusiastic about its promise to transform mobility and realize impressive societal benefits. This paper is an attempt to carefully examine the potential of AD to realize safety benefits, to challenge widely-held assumptions and to delve more deeply into the barriers that are hitherto largely overlooked. As automated vehicle (AV) technologies advance and emerge within a ubiquitous cyber-physical world they raise additional issues that have not yet been adequately defined, let alone researched. Issues around automation, sociotechnical complexity and systems resilience are well known in the context of aviation and space. There are important lessons that could be drawn from these applications to help inform the development of automated driving. This paper argues that for the foreseeable future, regardless of the level of automation, a driver will continue to have a role. It seems clear that the benefits of automated driving, safety and otherwise, will accrue only if these technologies are designed in accordance with sound cybernetics principles, promote effective human-systems integration and gain the trust by operators and the public.